2023
DOI: 10.3389/fphar.2023.1101728
|View full text |Cite
|
Sign up to set email alerts
|

The use of remimazolam versus propofol for induction and maintenance of general anesthesia: A systematic review and meta-analysis

Abstract: Background: The primary objective of this study was to compare the risk of hypotension, as well as the induction and recovery characteristics between remimazolam and propofol in patients receiving surgery under general anesthesia.Methods: The Embase, Medline, Google scholar, and the Cochrane Library databases were searched from inception to March 2022 for randomized controlled trials The primary outcome was the risk of post-induction hypotension between the two agents, while the secondary outcomes included ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 63 publications
3
26
2
Order By: Relevance
“…These results were confirmed by four meta-analyses that reported that remimazolam is more haemodynamically stable than propofol or midazolam during sedation 116–119 . A recent meta-analysis by Ko et al , 120 published 2 days after conducting our literature search, confirms the haemodynamic stability of remimazolam for induction of general anaesthesia when compared with propofol. It seems that all commonly used sedatives, except for dexmedetomidine, show better haemodynamic stability during sedation than propofol 121 .…”
Section: Discussionsupporting
confidence: 76%
“…These results were confirmed by four meta-analyses that reported that remimazolam is more haemodynamically stable than propofol or midazolam during sedation 116–119 . A recent meta-analysis by Ko et al , 120 published 2 days after conducting our literature search, confirms the haemodynamic stability of remimazolam for induction of general anaesthesia when compared with propofol. It seems that all commonly used sedatives, except for dexmedetomidine, show better haemodynamic stability during sedation than propofol 121 .…”
Section: Discussionsupporting
confidence: 76%
“…First, in our clinical study, although the doses of propofol and remimazolam were decided according to the manufacturer's instructions and based on the results of our previous study, 8 and the T LOC was comparable between the study groups, the BIS value was significantly higher in the remimazolam group than in the propofol group, especially at T 4 . Remimazolam‐based anaesthesia showed a higher BIS value than propofol‐based anaesthesia, despite comparable anaesthetic effects due to the nature of benzodiazepines 7,30,31 . However, this might have been a confounding factor in our study.…”
Section: Discussionmentioning
confidence: 62%
“…Remimazolam-based anaesthesia showed a higher BIS value than propofol-based anaesthesia, despite comparable anaesthetic effects due to the nature of benzodiazepines. 7,30,31 However, this might have been a confounding factor in our study. Second, we examined the haemodynamic effects of the studied drugs during the induction of general anaesthesia; however, the haemodynamics during surgery Male Wistar rats were purchased from Sankyo Laboratory Service Corporation (Sapporo, Japan), and rats aged 10-13 weeks were used in the experiments.…”
Section: Gene Expression Analysis Of Gaba a Receptor Subunits In Rat ...mentioning
confidence: 84%
“…It has better hemodynamic stability than other intravenous anesthetic agents except ketamine. [11,12] Also, it has less respiratory inhibition. however, unlike midazolam, it can be used for maintenance of anesthesia because it has a short context-sensitive half time.…”
Section: Discussionmentioning
confidence: 99%